2022
DOI: 10.3233/frl-200017
|View full text |Cite
|
Sign up to set email alerts
|

Curiosity and other attitudes towards sex robots: Results of an online survey

Abstract: As artificial intelligence and technology advance, mobile robots capable of human intimacy are an inevitable consequence of this progress. Such a profound shift in sexual technology will herald both advantages and disadvantages for human intimate relationships, yet a paucity of research exists on the study of human-robot sexual relationships. We believe a greater understanding of attitudes toward sex robots will be of value as this emerging technology progresses from its currently incipient stage. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
(51 reference statements)
2
4
1
Order By: Relevance
“…These findings contrast with evolutionary prediction 2 that males-at least those in heterosexual relationships-are more likely to be jealous of their partner being physically intimate with another person than women are [38,[71][72][73]. Instead, they are consistent with evidence that males are more positive than females to the idea of physically sophisticated sex technologies like sex robots [57,60].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…These findings contrast with evolutionary prediction 2 that males-at least those in heterosexual relationships-are more likely to be jealous of their partner being physically intimate with another person than women are [38,[71][72][73]. Instead, they are consistent with evidence that males are more positive than females to the idea of physically sophisticated sex technologies like sex robots [57,60].…”
Section: Discussioncontrasting
confidence: 75%
“…New or near-future artificially intimate technologies that deliver sophisticated emotional or physical engagement create new opportunities both for jealousy and for the study of how jealousy arises. Recent studies have shown that both participant sex [28,57,60] and the apparent "sex" of the technology [28] can influence how a participant anticipates the prospect of artificially intimate technologies, including how they anticipate jealousy. Even though these technolo-gies lack both their own interests and agency (but see [61]), they can appear to have both, and they offer a far more extensive user experience than older technologies like vibrators and social media platforms.…”
Section: Will Artificial Intimacies Affect the Lives Of Users Andmentioning
confidence: 99%
“…The point is that such humanoid sex robots are meant to dispossess Africans of their human spouses, who are thereby replaced with such humanoid sex robots. Brandon et al (2022, p. 11) write thus:Our results confirmed that men consistently report more positive reactions to sex with robots than women . .…”
Section: Beyond the Coloniality Of Power: The Complexity Of The Colon...supporting
confidence: 78%
“…In this regard, scare tactics were used to dispossess colonized peoples of their marriages and now colonialists are using bait tactics to market artificially intelligent humanoid sex robots such that those among the colonized who abandoned their marriages can now marry or buy humanoid sex robots to replace their original human spouses (Nhemachena, 2021b). Global capital is now manufacturing humanoid sex robots to replace human spouses, companion sex robots are being created and sold across the world, and sex dolls are being produced to replace original human spouses (Adekanye, 2020; Aoki & Kimura, 2021; Arafat & Kar, 2021; Brandon et al, 2022). Humanoid sex robots and sex dolls are being marketed in Africa on the assumption that Africans do not possess human spouses or companions and that therefore they must buy humanoid sex robots or sex dolls.…”
Section: Beyond the Coloniality Of Power: The Complexity Of The Colon...mentioning
confidence: 99%
“…Many studies have shown that the sex robot market is targeted almost exclusively at male consumers [ 45 , 46 , 47 ]. Furthermore, our society often has a limited view about female sexuality and reduces it to the procreational sphere.…”
Section: Pros and Cons Of The Spread Of Sex Robotsmentioning
confidence: 99%